Highly-Conductive, Transparent Ga-Doped ZnO Nanoneedles for Improving the Efficiencies of GaN Light-Emitting Diode and Si Solar Cell. (1st January 2020) - Yao, Yu-Feng; Lin, Chun-Han; Su, Chia-Ying; Tu, Charng-Gan; Liao, Jia-Yu; Yang, Shaobo; Teng, Chin-Chou; Tse, Wai Fong; Kiang, Yean-Woei; Yang, C. C.
Abstract : The growths of transparent, highly-conductive Ga-doped ZnO (GaZnO) nanoneedles (NNs) on the tops of GaN-based light-emitting diodes (LEDs) and Si solar cells for enhancing light extraction and reducing surface reflection, respectively, and hence increasing their efficiencies are demonstrated. The GaZnO NNs are grown based on the vapor-liquid-solid process by using surface Ag nanoparticles (NPs) as growth catalyst. In the application to LED, the residual Ag NPs can induce the surface plasmon (SP) coupling effect for increasing the LED emission efficiency. By combining the SP coupling effect, the light extraction effects of the GaZnO NNs and simultaneously deposited GaZnO thin film, and the current spreading effect of the thin film, the LED output intensity can be increased by 100%. In the solar cell application, the SP resonance of the residual Ag NPs can also enhance sunlight harvest and hence the energy conversion efficiency. By combining the effects of the residual Ag NPs, the GaZnO thin film, and the GaZnO NNs, the energy conversion efficiency of a Si solar cell can increase from 9.65 to 12.30%, corresponding to a relative enhancement of 27.5%.